Coexistence of congenital red cell pyruvate kinase and band 3 deficiency - Branca, Rosa (2004)
The authors report the case of a 9-year-old Caucasian girl, born in northern Portugal, with chronic nonspherocytic haemolytic anaemia and without family history of anaemia. The aethiological study of this anaemia revealed pyruvate kinase deficiency (PKD), because of two previously described mutations (426Arg fi Trp and 510Arg fi Gln). Since the blood smear revealed features not fully compatible with PKD diagnosis, additional tests were performed for the propositus and her parents, namely red blood cell membrane protein analysis. A decrease in proteins band 3 (15%) and 4.2 (18%) was found in the propositus. Her father presented only a decrease in band 3 (11%). Coexistence of PKD and erythrocyte membrane proteins deficiency in the same patient is very uncommon. Our findings suggest that a careful blood smear observation may lead to the identification of a combined deficiency in erythrocyte membrane proteins and enzymopathies.